Participatory Learning : Religious Education in a Globalizing Society - Hermans, Chris, (Empirical Studies in Theology ;, 2003)
In many respects children and youths receiving religious instruction in our culture resemble extraterrestrial beings doing an orientation course. Religion and religiosity are unknown quantities which they have hardly encountered at home. Religion seems something else, something greater. This book is a study of the foundations of religious education, centered around six concepts: religion in a globalizing society, religious tradition, religion, the religious self, learning through participation and interreligious learning.